The Effect of Exercises According to the Posner Model in Developing the Skill of Blocking Volleyball for Juniors - Mohamed Abdel-Ridha Jallod; Muwafaq Sinikh Jaafar (دراسات وبحوث التربية الرياضية, 2023)
The researchers discussed the importance of research in keeping pace with the development in using the Posner model in developing the blocking skill to be prepared in a manner commensurate with the development in the game in general and in defensive skills in particular, As for the research problem, it was represented by the presence of fluctuation in the actual performance of the players, or their mastery of certain skills and not others, which may affect the actual performance and the overall result of the game, The researchers used the experimental method, As for the research sample of (30) players, it consisted of two clubs (Al-Madina and Al-Chibayish). The researchers prepared an educational curriculum that lasted (10) weeks. They conducted pre and posttests for the two research groups, and found appropriate statistical coefficients for them, and the results were discussed in the light of statistics. The most important conclusions and the most important recommendations were: The exercises prepared according to the Posner model contributed to the development of the accuracy of the blocking skill in volleyball for juniors, The researchers recommended the need Follow the scientific foundations, methods and methods to develop educational and training curricula that will develop and improve the level of skillful performance, especially among young volleyball players, to find out their real levels.